Tax avoidance in the Indonesian manufacturing industry - Manihuruk, Ricardo Samuel; Arieftiara, Dianwicaksih; Miftah, Munasiron (Journal of Contemporary Accounting, 2021)
This study aims to determine tax avoidance in the Indonesian manufacturing industry. The control variable is the industrial sub-sector. In this study tax avoidance is proxied as book tax differences. This study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. Using the STATA 13 regression data panel, this study shows that capital intensity has no significant effect on tax avoidance and inventory intensity has no significant effect on tax avoidance. However, this study found that industry auditors' specialization had a positive effect on tax avoidance. This study contributes to enhancing empirical evidence of audit quality, proxied by industry auditors' specialization can provide assurance of managers' tax avoidance activities did not violate the fairness principle, thus increase tax avoidance activities.